Peran Teknologi Dalam Manajemen Risiko Dan Inovasi - Lailam Baridah; Nola Putri Ritonga; Sakina Nur Aini (Journal on Education, 2025)
The role of technology in risk management and innovation is crucial in the modern business world, where uncertainty and rapid change are key challenges. This article discusses how technology plays a role in identifying, analyzing, and mitigating risks, as well as accelerating and improving the effectiveness of the innovation process. In risk management, technologies such as big data, predictive analytics, the Internet of Things (IoT), artificial intelligence (AI), and integrated risk management systems enable organizations to monitor and address potential risks more efficiently. Meanwhile, in terms of innovation, technology supports the creation of new products and services, accelerates the development process, and opens up opportunities for global collaboration. Innovation can also introduce new business models that are more adaptive to market changes. The synergy between risk management and innovation through the use of technology helps organizations not only survive but also thrive amidst increasingly fierce challenges and competition. This article highlights the importance of technology adoption as a key to managing uncertainty and creating new value in an ever-changing business world.